LEGAL PROTECTION FOR THE PUBLIC AGAINST ONLINE JOB VACANCY FRAUD - Atika Sandra Dewi; Isdiana Syafitri; Tarmizi; Muhammad Husni; Daud; Nufaris Elisa; Ayu Aranti Zuhri Ritonga (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Abstract: Online job vacancy fraud is a form of cybercrime that exploits the development of digital media and the high demand for jobs in society. Low legal and digital literacy levels cause people to become victims of various fraudulent methods, such as online job vacancies, misuse of personal data, and use of company identities. This Community Service Activity aims to increase public understanding of legal protection against online job vacancy fraud through legal counseling and digital literacy education. The implementation of the activity was carried out with a participatory approach through material delivery, discussions, and questions and answers that actively involved the community. The results of the activity showed that participants gained a better understanding of how to recognize the characteristics of official job vacancies, verify recruitment information, maintain the security of personal data, and understand the legal remedies that can be taken if they become victims of fraud. This activity is expected to increase legal awareness and digital literacy in the community as a preventive measure in minimizing the risk of online job vacancy fraud.